2008
DOI: 10.1210/jc.2007-2843
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid and Umbilical Cord Plasma Corticotropin-Releasing Factor (CRF), CRF-Binding Protein, Adrenocorticotropin, and Cortisol Concentrations in Intraamniotic Infection and Inflammation at Term

Abstract: Context: Pregnant tissues express corticotropin-releasing factor (CRF), a peptide modulating fetal and placental ACTH and cortisol secretion. These actions are modulated by the locally expressed CRF-binding protein (CRF-BP).Objective: The objective of the study was to determine whether CRF, CRF-BP, ACTH, and cortisol concentrations change in amniotic fluid and umbilical cord plasma in the presence of intraamniotic infection/inflammation (IAI) in women with spontaneous labor at term.Design: This was a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
(58 reference statements)
0
8
1
Order By: Relevance
“…The observation that Gram-negative rods were the most frequently found microorganisms in MSAF is in contrast to previous studies (both term and preterm gestations) reported by our group [73,125–152] and others [117,153167], in which the most frequent microorganisms isolated from the amniotic fluid were genital Mycoplasmas (in particular, Ureaplasma species). One possible explanation for this finding is that Gram-negative bacteria may be a more potent inducer of bowel peristalsis and meconium passage into the amniotic fluid than other microorganisms.…”
Section: Discussioncontrasting
confidence: 99%
“…The observation that Gram-negative rods were the most frequently found microorganisms in MSAF is in contrast to previous studies (both term and preterm gestations) reported by our group [73,125–152] and others [117,153167], in which the most frequent microorganisms isolated from the amniotic fluid were genital Mycoplasmas (in particular, Ureaplasma species). One possible explanation for this finding is that Gram-negative bacteria may be a more potent inducer of bowel peristalsis and meconium passage into the amniotic fluid than other microorganisms.…”
Section: Discussioncontrasting
confidence: 99%
“…However, we note that the pattern of differences in the p CRH trajectory by CT status in our study is of similar nature and magnitude to what has previously been reported in pregnancies complicated by preeclampsia and preterm birth (70, 71). Additional support for the biological plausibility of our hypothesis that p CRH physiology may act as a mediator of intergenerational transmission of the effects of maternal CT exposure derives from the observation that many of the adverse pregnancy, fetal, birth and postnatal outcomes associated with p CRH dysregulation in pregnancy (such as intra-amniotic infection (72), growth and size at birth (46), preterm delivery (46, 71), difficult infant temperament (42), and obesity (44),) are antecedents of the same alterations in stress physiology systems and neurodevelopmental disorders that are manifest in children of CT+ mothers (1521). …”
Section: Discussionmentioning
confidence: 82%
“…Secretion of p CRH is directly stimulated by pro-inflammatory cytokines such as IL -1 and microbial antigens (84). CRH, in turn, has been shown to have a pro-inflammatory effect in the periphery (85, 86), and increased levels of p CRH have been associated with intra-amniotic infection (72, 87). Moreover, previous studies of non-pregnant CT+ women have reported they exhibit an increased inflammatory status (8890).…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that assessed amniotic CRH (Emanuel et al, 1994;Florio et al, 2008;Laatikainen et al, 1988;Menon, Arora, Hobel, & Fortunato, 2008;Salminen-Lappalainen & Laatikainen, 1990;Stalla et al, 1989;Torricelli et al, 2009) or UCN (Iavazzo et al, 2009;Imperatore et al, 2006;Torricelli et al, 2009) did not include any psychological stress variables. The current study, therefore, expands our knowledge and corroborates the theoretical assumption and evidence from previous investigations (Chen et al, 2010;Hobel et al, 1999;Latendresse & Ruiz, 2010;Mancuso et al, 2004;Tse et al, 2012) that maternal chronic stress leads to abnormal increases in fetoplacental CRH secretion.…”
Section: Discussionmentioning
confidence: 99%